2015
DOI: 10.1016/j.bbamcr.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-sensing receptor: A promising target for prevention of colorectal cancer

Abstract: The inverse correlation between dietary calcium intake and the risk of colorectal cancer (CRC) is well known, but poorly understood. Expression of the calcium-sensing receptor (CaSR), a calcium-binding G protein-coupled receptor is downregulated in CRC leading us to hypothesize that the CaSR has tumor suppressive roles in the colon. The aim of this study was to understand whether restoration of CaSR expression could reduce the malignant phenotype in CRC.In human colorectal tumors, expression of the CaSR negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 46 publications
0
59
0
Order By: Relevance
“…In order to test whether the CaSR mediates also the effect of [Ca 2+ ] o on replication licensing we used the HT29 cell line stably transfected either with the full length CaSR (HT29 CaSR ) or with an empty vector (HT29 Emp ). In contrast to Caco-2 cells, parental HT29 cells are not responsive to the antiproliferative effect of [Ca 2+ ] o [33] and express undetectable levels of CaSR [34]. The HT29 CaSR cells overexpressing the CaSR, expressed significantly lower levels of CDT1, CDC6, CDC45, and MCM2 compared with the HT29 Emp controls (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…In order to test whether the CaSR mediates also the effect of [Ca 2+ ] o on replication licensing we used the HT29 cell line stably transfected either with the full length CaSR (HT29 CaSR ) or with an empty vector (HT29 Emp ). In contrast to Caco-2 cells, parental HT29 cells are not responsive to the antiproliferative effect of [Ca 2+ ] o [33] and express undetectable levels of CaSR [34]. The HT29 CaSR cells overexpressing the CaSR, expressed significantly lower levels of CDT1, CDC6, CDC45, and MCM2 compared with the HT29 Emp controls (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…However, in the context of colorectal cancer and parathyroid tumors, higher CaSR expression has been observed to be protective (26). In colorectal cancer, activation of CaSR promotes E-cadherin expression and down-regulates the Wnt/␤-catenin pathway (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, subsequent studies demonstrated that the CaSR recognizes other ligands and is expressed in many other tissues and organs, including the gastrointestinal tract, brain, pituitary, thyroid, skin, breast, pancreas, lung, bone, and heart [2], suggesting that this receptor plays additional, yet less well defined, physiological roles in the regulation of normal and abnormal cell function [3,4,5,6]. Indeed, recent evidence indicates that the CaSR is implicated in the negative control of colon cell proliferation [7] and cancer [8], nutrient sensing [4], epithelial transport [9], inflammation [10], bone turnover [11] and stem cell differentiation [6]. Thus, the signaling mechanisms triggered via CaSR activation are attracting intense attention.…”
Section: Introductionmentioning
confidence: 99%